Fantasía y conciencia estética: El estatuto fenomenológico de la imagen - Mendoza-Canales, Ricardo (2020)
“Phantasy and Aesthetic Consciousness: the Phenomenological Status of the Image”. This article aims to establish first a double distinction: on the one hand, between phantasy and image consciousness, on the other hand, between phantasy and aesthetic consciousness, both stemming from the works of Edmund Husserl. Both series of distinctions are connected by the special status that Husserl gave to the image, which is to be subject of explanation too. The article proposes three conclusions: that the so-called “aesthetic consciousness” is not the result of any Epoché; that the image experience intermingles phantasy and perception, and that this aesthetic consciousness (“imagination” in a wide sense) demands as its counter-pole a subject (the phantasy-Ego) who inhabits the irreality of the “as if”.